Analysis Of Radio Spot For The Cigarette And Tobacco Tax Initiative (Tufts Archival Research Center, 2007)
Memorandum from Californians Against Unfair Tax Increases, a committee sponsored by the tobacco industry, regarding an analysis of a TV and radio spot for the Cigarette and Tobacco Tax Initiative. Provides a line-by-line analysis of the radio spot, emphasizing the wrongfulness of a tax increase because it disproportionately burdens working families.